2021
DOI: 10.3390/molecules26206106
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and Highly Directional Visible Light Scattering by Laser-Splashed Lossless TiO2 Nanoparticles

Abstract: All-dielectric nanoparticles, as the counterpart of metallic nanostructures have recently attracted significant interest in manipulating light-matter interaction at a nanoscale. Directional scattering, as an important property of nanoparticles, has been investigated in traditional high refractive index materials, such as silicon, germanium and gallium arsenide in a narrow band range. Here in this paper, we demonstrate that a broadband forward scattering across the entire visible range can be achieved by the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Similar findings were reported by Y. Zhang et al [ 50 ] . They numerically confirmed that the FWD/BWD scattering ratio peak of vertical TiO 2 nanowires redshifts with increasing length.…”
Section: Resultssupporting
confidence: 92%
“…Similar findings were reported by Y. Zhang et al [ 50 ] . They numerically confirmed that the FWD/BWD scattering ratio peak of vertical TiO 2 nanowires redshifts with increasing length.…”
Section: Resultssupporting
confidence: 92%